DINAMICS OF THE DIABETIC FOOT. CLINICAL OUTCOMES (DIABETIC FOOT) IN HYPERTENSIVES WITH TYPE 2 DIABETES BEFORE AND AFTER IMPLEMENTATION OF GUIDELINES ON MANAGEMENT IN KAZAKHSTAN - Zh. Akimbaeva; Zh. Akanov; Т. Meimanaliev (Российский кардиологический журнал)
Aim. To analyze the dynamics or diabetic foot prevalence depending on the sex of patients. To study clinical outcomes of diabetic foot in hypertensives with diabetes type 2 (DM) before and after implementation of the management protocols (MP) for arterial hypertension (AH) and DM. Material and methods. Totally, data on 13737 patients included, from SouthKazakhstan region (SKR), and 118131 patients aged 18 y. o. and older. The study was done based on the retrospective database analysis of Republic Center of Healthcare development of the Ministry of Health and Social development of Kazakhstan Republic (RK) from 2000 to 2014 y. Results. The number of clinical outcomes as diabetic foot in AH with DM patients among males 18 y. o. and older, remained almost unchanged in SKR during the studied period (2000-2014), and in RK the number reduced, respectively, from 9,7% to 7,4% (p>0,05). Conclusion. After implementation of diagnostics and management protocols, in 2006-2014y. there was decrease of the part of diabetic foot cases, of disability and mortality among the patients with AH and DM, both sexes, in SKR and in the entire RK.